2020
DOI: 10.1371/journal.pone.0227587
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the strategy of micro-environmental adaptation: Transcriptomic analysis of two alvinocaridid shrimps at a hydrothermal vent

Abstract: Diffusing fluid at a deep-sea hydrothermal vent creates rapid, acute physico-chemical gradients that correlate strongly with the distribution of the vent fauna. Two alvinocaridid shrimps, Alvinocaris longirostris and Shinkaicaris leurokolos occupy distinct microhabitats around these vents and exhibit different thermal preferences. S. leurokolos inhabits the central area closer to the active chimney, while A. longirostris inhabits the peripheral area. In this study, we screened candidate genes that might be inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 59 publications
1
8
1
Order By: Relevance
“…In addition, the water of hydrothermal vent area with lower pH (5.20 and 5.50) are more acidic than those of the seep. In this study, it has been revealed that Campylobacteria and Gammaproteobacteria are the most dominant microbial community compositions of the alvinocaridid gills, consisting with other studies in crustaceans from vent and seep environments ( Hügler et al, 2011 ; Sun et al, 2016 ; Zhang et al, 2018 ). Among them, Sulfurovaceae (all Sulfurovum ) is ubiquitous in all samples, which is usually sulfur oxidizer and reducer and plays a vital role in the sulfur, nitrogen, hydrogen cycles, and even bio-fixation of CO 2 in the deep sea ( Mino et al, 2014 ; Kwon et al, 2015 ; Jeon et al, 2017 ).…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…In addition, the water of hydrothermal vent area with lower pH (5.20 and 5.50) are more acidic than those of the seep. In this study, it has been revealed that Campylobacteria and Gammaproteobacteria are the most dominant microbial community compositions of the alvinocaridid gills, consisting with other studies in crustaceans from vent and seep environments ( Hügler et al, 2011 ; Sun et al, 2016 ; Zhang et al, 2018 ). Among them, Sulfurovaceae (all Sulfurovum ) is ubiquitous in all samples, which is usually sulfur oxidizer and reducer and plays a vital role in the sulfur, nitrogen, hydrogen cycles, and even bio-fixation of CO 2 in the deep sea ( Mino et al, 2014 ; Kwon et al, 2015 ; Jeon et al, 2017 ).…”
Section: Discussionsupporting
confidence: 75%
“…Moreover, vents are usually richer in hydrogen sulfide and heavy metals than those of seeps ( Cosson & Vivier, 1997 ; Miyazaki et al, 2013 ). In addition, the temperature of the hydrothermal fluid can reach over 400 °C, and a steep thermal gradient is specifically created by mix of the vent fluid and the surrounding seawater (∼2 °C) ( Koschinsky et al, 2008 ; Zhu et al, 2020 ), while in seeps, temperatures do not vary appreciably from those of the ambient deep-sea water.…”
Section: Introductionmentioning
confidence: 99%
“…Collagen is the main structural protein in the extracellular matrix of diverse connective tissues, playing important roles in tissue morphogenesis and the maintenance of tissue structural integrity ( Gelse et al., 2003 ). Previous studies uncovered that some collagens are positively selected in the deep-sea fish Aldrovandia affinis ( Lan et al., 2018 ) and the deep-sea alvinocaridid shrimp Shinkaicaris leurokolos ( Zhu et al., 2020 ), suggesting their potential roles in deep-sea adaptation. Herein, 86 collagen-encoding transcripts were identified, with 19 upregulated and 4 downregulated in the onboard fixed group ( Table S2 ).…”
Section: Resultsmentioning
confidence: 99%
“…The RNA extraction, sequencing, assembly, and annotation were performed according to our laboratory's published paper [33]. Based on the sequences of the annotated Crustins, two paired primers of Crustins, Al-crus 3 and Al-crus 7, were designed (Table S1).…”
Section: Gene Cloning Of Al-crus 3 and Al-crusmentioning
confidence: 99%